"Using what you have" to teach for global citizenship. Issue 1 (15th June 2021) - Christoff, Andrea
Abstract : Purpose: This case study illustrates how one social studies teacher used the International Baccalaureate (IB) Middle Years Programme (MYP)' s framework and philosophy to teach for global citizenship. The research question that framed this study was: How is an IB MYP Individuals and Societies (I&S) teacher enacting their perceptions and understanding of global citizenship education? Findings illustrate that this teacher enacted a proactive pedagogy, using her own personal perceptions and what IB MYP offered her through their affective and cognitive frameworks to apply her conceptions of global citizenship education. Design/methodology/approach: The data for this single case study came from teacher semi-structured interviews (Rubin and Rubin, 2012), observations, field notes (Merriam and Tisdell, 2016) and teacher created documents. The goal for the teacher created documents was to provide detail, depth and evidence to support or contrast with what was found in the interviews and observations. Simultaneous, in vivo, and values coding were used to analyze the data and to get an overall picture of what the participant said, believed and practiced. Theories surrounding global citizenship education provided the lens for the study. Findings: The findings are organized according to (1) the way this teacher's developed constructions of global citizenship and global citizenship education and IB led her to use the IB philosophy and framework to shape her beliefs and practices and (2) the way she embraced the tensions and possibilities inherent in her teaching for global citizenship in an IB MYP classroom to teach a proactive form of global citizenship education. Research limitations/implications: This research provides insight into the curriculum framework of IB MYP and the curriculum and instruction decisions of an I&S teacher. For the global citizenship education field, this study provides an example of how global citizenship can be incorporated into a social studies classroom. Practical implications: For social studies education, this study uncovered the possibilities present in the curriculum when a teacher is given the space to make their own instructional decisions. This study also gives guidance on how international curriculum frameworks can be utilized for global citizenship education. Finally, this study illustrates teachers must fully subscribe to IB and the MYP as a means of teaching for global citizenship for it to be beneficial. Originality/value: This study has value because it highlights how a social studies teacher successfully uses an international curriculum framework to teach for global citizenship. Few studies have shown examples of teachers, especially IB MYP teachers, who are committed to teaching for global citizenship and use the tools they are given to center student choice and connect the content to their students' lives. Teachers and researchers will be able to view the pedagogical possibilities inherent in this teacher's global citizenship methods.